Female Consciousness in Torday's Salmon Fishing in the Yemen - Baleid Taha Shamsan Saeid (Taez University, 2019)
Salmon Fishing in the Yemen is a representative work by Paul Torday, a famous modern novelist who has greatly influenced readers with his ideas. This research investigates the female consciousness in Salmon Fishing in the Yemen and analyses the female qualities that strengthen the position of women in the male-dominated society.    The researcher aims at investigating the female consciousness traits which include independent thoughts, feminine ideality, essence of independence, essence of individuality, family affairs, maturity, intellectual thoughts, love and the pursuit of self-privacy. These traits are highlighted in detail together with other female features that accompany the female characters in the novel and how they help creating a modal feminine character who has engraved a strong image in the world of man.     Woman uses her independent thoughts to create an unequal image possessing qualities of self-reliance, strong spirit, strong persistence and certainty of success. It is the female consciousness that lets woman struggles to be an obstinate rival for man.     In the present study, Ms. Hester and Mrs. Mary have been chosen to be the representative of those woman who carry out the female consciousness in this novel and try to present a positive model of femininity. Ms. Hester, under her self-control and certainty epitomizes the power of patience, tolerance, optimism and success.  Mrs. Mary, on the other hand, protests against the male weak-spirited attitude by leaving home for the sake of self-proving.